Peran Parenting Self Efficacy Orang Tua Pada Perkembangan Anak Usia Dini Di Kelompok B - Nur Anisa Korua; Irvin Novita Arifin; Sri Wahyuningsi Laiya (Student Journal of Early Childhood Education, 2023)
This study aims to gather data and information about Parenting self-efficacy, which refers to parents' confidence in their ability as parents. The study uses a qualitative descriptive approach and involves 10 parents as research subjects. The method comprised observation, interviews, and documentation. The findings on the role of parenting self-efficacy in early childhood development conclude that parents with high parenting self-efficacy were better at supporting their children's positive development compared to parents with low parenting self-efficacy. The important role in early childhood development lies in confident parents who tend to provide appropriate attention, stimulation, and support for their child's development. Confident parents are more effective in providing cognitive stimulation and building positive social relationships with their children. Early childhood is a crucial period in an individual's life, and parental involvement plays a significant role.